Do former college athletes earn more at work? A nonparametric assessment - Daniel J. Henderson; Alexandre Olbrecht; Solomon W. Polachek (Institute for the Study of Labor (IZA), 2005)
This paper investigates how students' collegiate athletic participation affects their subsequent labor market success. It uses newly developed distributional tests to establish that the wage distribution of former college athletes is significantly different from non-athletes and that athletic participation is a significant determinant of wages. Additionally, by using newly developed techniques in nonparametric regression, it shows that on average former college athletes earn a wage premium. However, the premium is not uniform, but skewed so that more than half the athletes actually earn less than non-athletes. Further, the premium is not uniform across occupations. Athletes earn more in the fields of business, military, and manual labor, but surprisingly, athletes are more likely to become high school teachers, which pays a relatively lower wage to athletes. We conclude that nonpecuniary factors play an important role in occupational choice, at least for many former collegiate athletes.
Keywords: C14; J10; J30; J40; L83; 330; nonparametric; generalized Kernel estimation; wage determination; earnings; sports economics; athletics; Akademische Berufe; Sportler; Gehalt; Schätzung; USA